Investigations on Human Rights Awareness among B. Ed Level Prospective Teachers based on the Demographic and Academic Characteristics - et. al., Rakshita Kandpal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human rights awareness through education is the ultimate solution against Human Rights abuses. Human Rights awareness of teacher–trainees will help to understand and to expand the rights of their future students. That’s why the particular study was preferred. The study was conducted to investigate the awareness of Human Rights among B. Ed level teacher trainees. 80 B. Ed level teacher- trainees were selected through purposive sampling method from the department of Education, S.S.J. University, Almora, Uttarakhand. To study the human rights awareness in groups of teacher trainees identified based on demographic and academic factors i.e. gender, nature of residence, academic stream, marital status, and educational status. For data collection, a self-made Human Rights Awareness Questionnaire (HRAQ) was used by the researcher based on 5 aspects of human rights and then percentage analysis of data was done. A finding of the study revealed that female, rural, Arts-stream, unmarried, and postgraduate level teacher-trainees were found more aware of human rights.